2013
DOI: 10.1186/1559-4106-8-12
|View full text |Cite
|
Sign up to set email alerts
|

Efficient surface functionalization of wound dressings by a phytoactive nanocoating refractory to Candida albicans biofilm development

Abstract: The present study reports the fabrication and characterization of a novel nanostructured phyto-bioactive coated rayon/ polyester wound dressing (WD) surface refractory to Candida albicans adhesion, colonization and biofilm formation, based on functionalized magnetite nanoparticles and Anethum graveolens (AG) and Salvia officinalis (SO) essential oils (EOs). TEM, XRD, TGA, FT-IR were used for the characterization of the fabricated nanobiocoated WDs. Using magnetic nanoparticles for the stabilization and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The authors indicate that the maximum efficiency of the AG at 48 h and of SO at 72h may be explained by the different release rates of the two phytocompounds from the nanoparticle carrier. This experiment stated that the antibiofilm effect of nanophytoactive coated wound dressings is due to the presence of essential oils, since wound dressings coated with magnetite nanoparticles only proved no significant antibiofilm activity [67]. The prolonged anti-fungal effect could be due to the fact that the highly volatile essential oils are stabilized by the functionalized magnetite nanoparticles, which are thus acting as efficient carriers and also ensuring a controlled release of the active phytocompounds, coupled with lower cytotoxicity and biodegradability.…”
Section: Nanotechnological Approaches For Im-proving Modulators Bio-amentioning
confidence: 96%
See 2 more Smart Citations
“…The authors indicate that the maximum efficiency of the AG at 48 h and of SO at 72h may be explained by the different release rates of the two phytocompounds from the nanoparticle carrier. This experiment stated that the antibiofilm effect of nanophytoactive coated wound dressings is due to the presence of essential oils, since wound dressings coated with magnetite nanoparticles only proved no significant antibiofilm activity [67]. The prolonged anti-fungal effect could be due to the fact that the highly volatile essential oils are stabilized by the functionalized magnetite nanoparticles, which are thus acting as efficient carriers and also ensuring a controlled release of the active phytocompounds, coupled with lower cytotoxicity and biodegradability.…”
Section: Nanotechnological Approaches For Im-proving Modulators Bio-amentioning
confidence: 96%
“…It is well known that S. officinalis (SO) and A. graveolens (AG) essential oils perform antiseptic properties and low side effects; therefore many studies suggest them as excellent alternatives for developing antimicrobial strategies [67]. Recent evidence reveals the utility of novel nanophytoactive coated wound dressings, which have been tested in vitro for their antibiofilm activity, using both qualitative (SEM examination) and quantitative (viable cells embedded in biofilm) approaches.…”
Section: Nanotechnological Approaches For Im-proving Modulators Bio-amentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetal extracts and essential oils have been extensively used in traditional medicine for treating infections (WHO, 2002). Recent studies revealed the great impact of mixture extracts and pure compounds obtained from Angiosperms and Gymnosperms to impair bacteria growth and also to modulate their virulence and resistance (Saviuc et al, 2013;Anghel and Grumezescu, 2013;Anghel et al, 2013a). Despite their proven role, studies revealed that natural compounds usually have low stability, and the technical procedures necessary for their testing and use significantly reduce their antimicrobial effect, especially when used in low doses (Holban et al, 2014b).…”
Section: Introductionmentioning
confidence: 96%
“…In the past years a series of papers have been published in prestigious journals highlighting the relevance of magnetite nanostructures in preventing the development of microbial biofilm and the opportunity of utilizing these nanosystems to obtain improved, antimicrobial coatings for biomedical applications [78]. Nonpolar functionalized magnetite nanostructures alone [910] or combined with different natural products, such as usnic acid (UA) [11] or essential oils ( Mentha piperita [12], Anethum graveolens [13], Salvia officinalis [14], Eugenia carryophyllata [15]), showed improved antibiofilm effects on different types of microbial strains. Usually, these types of phyto-nano-coatings have been applied to a variety of medical surfaces in order to improve their resistance to microbial colonization [16].…”
Section: Introductionmentioning
confidence: 99%